2017
DOI: 10.15537/smj.2017.12.20516
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of specific natural substances on oral health

Abstract: Substances that are consumed daily or occasionally may influence an individual’s oral health. Some substances, such as alcohol, tobacco, and areca nut, adversely affect the oral region. However, some other substances, such as honey and green tea, which have antimicrobial properties, and berries, which have anticarcinogenic potential, exhibit beneficial effects on oral health. The effectiveness of synthetic drugs in maintaining oral health cannot be ignored; however, the benefits of synthetic drugs are associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…However the therapy alone does not restore all the gingival tissues and supplementary aids are used as adjuvant to ultrasonic scaling. [41,42].A bundle of studies have claimed favorable effects of natural products like olive oil, almond oil, green tea, propolis, honey and aloe vera [42][43][44][45][46][47] In this study we observed synergistic effects of gingival massage with two naturopaths that is aloe-vera gel and sidr honey compared with control group.105 participants of gingivitis with 3 loss to follow-up were reported in our research. mean age reported in our study is 48.6 ± 8.6 which is similar to a survey in United States which reported higher prevalence of gingivitis in adults with mean age as > 30 years [48].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However the therapy alone does not restore all the gingival tissues and supplementary aids are used as adjuvant to ultrasonic scaling. [41,42].A bundle of studies have claimed favorable effects of natural products like olive oil, almond oil, green tea, propolis, honey and aloe vera [42][43][44][45][46][47] In this study we observed synergistic effects of gingival massage with two naturopaths that is aloe-vera gel and sidr honey compared with control group.105 participants of gingivitis with 3 loss to follow-up were reported in our research. mean age reported in our study is 48.6 ± 8.6 which is similar to a survey in United States which reported higher prevalence of gingivitis in adults with mean age as > 30 years [48].…”
Section: Discussionsupporting
confidence: 57%
“…The anti-in ammatory action of honey gives the soothing effect on topical applications [25]. The antioxidants present in honey along with the antiin ammatory action prevent the deterioration of gingival and periodontal tissues [18][19][20][26][27][28][29].…”
mentioning
confidence: 99%
“…Key to the prevention of dental diseases is maintenance of good oral hygiene. Herbal extracts have received special attention because of being non-chemical and non synthetic in nature, and have been used in traditional medicine [36][37][38][39]. Interest in natural based toothpastes has increased since…”
Section: Resultsmentioning
confidence: 99%